SPATIAL DISTRIBUTION OF SOIL AVAILABLE NUTRIENTS IN THE POTATO GROWING POCKETS OF HOSHIARPUR DISTRICT OF PUNJAB - Jatav, M K; Dua, V K; Kumar, Manoj; Trehan, S P; Kumar, Sushil (Potato Journal, 2013)
Soil samples of potato growing pockets of Hoshiarpur district of Punjab were collected and analysed for pH, OC and available NPK. The soil analysis data was fed into GIS software and spatial maps generated. The soils of the district in general, were slightly acidic to slightly alkaline in reaction. The pH of collected soil samples varied from 5.0 to 8.2 with a mean value of 6.8. About 90 per cent of the total area had pH less than 7.5, a situation considered much suitable for potato cultivation. The organic carbon ranged from low to medium (0.2 to 0.7%) with an average value of 0.4 per cent. Available nitrogen ranged from 186.3 to 355.6 kg/ ha with mean value of 242.5 kg/ ha and more than 88 per cent samples had available phosphorus greater than 20 ppm. None of the collected sample was deficient in available phosphorus, suggesting build-up of P fertilizers in these areas. In case of available soil potassium, 79, 19.2 and 2 per cent samples were found to be low, medium and high, respectively. After kriging, results showed that 30.5 and 18.8% area had high and very high phosphorus, respectively, but low in nitrogen and potassium. About 17.3 per cent area was medium in available nitrogen, very high in phosphorus but low in available potassium, while 12.8% area was medium in both available N and K but very high in P.